Das zukunftsbezogene Futurperfekt. : Eine Untersuchung seiner Gebrauchsbedingungen auf Basis der Belege in den DWDS-Kernkorpora mit einem Ausblick auf das Präsensperfekt - Gärtig-Bressan, Anne-Kathrin (Linguistik Online, 2026)
This article tries to shed some light on the German Futurperfekt tense in its temporal use. On the basis of its occurences in two corpora of contemporary German, the DWDS-Kernkorpus 21 and the DWDS-Kernkorpus for the period after 1945, it analyses 1) the distribution of the examples among the text types in the corpora, 2) the occurences in main and subordinate clauses, 3) the mechanisms that ensure the temporal interpretation, 4) the presence of temporal expressions to fix the reference point and their temporal distance, 5) eventual modal factors inherent to the tense and 6) the frequency of telic and atelic verbs that occur in the tense. For each parameter, a comparison is made with occurrences for the Präsensperfekt tense, extracted from the DWDS-Kernkorpus 21.